Sewing Clothes, Weaving Meaning: A Qualitative Study of Fashion Shows as Transformative Learning in Vocational Schools of Fashion Design - Fujaatul Hayyina; Widiyanti Widiyanti; Nurul Hidayati; Agus Sunandar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Fashion shows in vocational education of Fashion Design in SMK have the potential as an integrative contextual learning media to build students' technical and nontechnical skills holistically. This study aims to examine the contribution of fashion shows to the development of creativity, communication, collaboration, product management, as well as the competence of design, textiles, patterns, and sewing techniques of students. Using a qualitative case study approach with in-depth interview techniques, observation, and visual documentation, the research was conducted at SMKN 3 Malang with five main informants. Data were analyzed through the Miles and Huberman model and member checking validation. The results show that student involvement in fashion shows encourages the exploration of market-relevant design ideas, structured teamwork, collective conflict resolution, and increased technical literacy through the use of digital technology. Teachers played an active role in production management and quality evaluation, while students showed increased confidence and work readiness. The activity also strengthened professional portfolios and networks through participation in events such as Malang Fashion Week. In conclusion, the fashion show proved to be a transformative learning platform that bridges the classroom and the industrial world. Future research is recommended to explore the impact of industry events on students' career networks across skill programs.